How Informed Are Actively Trading Institutional Investors? Evidence from Their Trading Behavior before a Break in a String of Consecutive Earnings Increases - KE, BIN; PETRONI, KATHY (Journal of Accounting Research, 2004)
ABSTRACT We examine whether transient institutional investors (i.e., institutions that trade actively to maximize short‐term profits) have information that allows them to predict a break in a string of consecutive quarterly earnings increases and thereby avoid the economically significant negative stock price response associated with the break announcement. We show that transient institutions predict the break at least one quarter in advance of the break quarter. We also provide evidence that is consistent with transient institutions obtaining information regarding the impending break from private communications with management.